Immune Cells on the Donor Corneal Endothelium After Corneal Transplantation. Issue 9 (September 2018) - Okumura, Naoki; Inoue, Ryota; Nakano, Shinichiro; Imai, Hirofumi; Matsumoto, Daiki; Kayukawa, Kanae; Wakimasu, Koichi; Kitazawa, Koji; Koizumi, Noriko; Kinoshita, Shigeru
Abstract : Purpose: The aim of this study was to investigate the existence of presumed immune cells observed by contact specular microscopy in patients who underwent penetrating keratoplasty (PK) and Descemet stripping automated endothelial keratoplasty (DSAEK). Methods: This cross-sectional study was conducted on consecutive patients who underwent follow-up visits between January and March 2015 for previously performed PK or DSAEK. Presumed immune cell–suspected "cell-like white dots" were evaluated by scanning slit contact specular microscopy. The association between the grading of presumed immune cells with clinical parameters, such as corneal endothelial cell density, time after surgery, and the titer of steroid administration, was also investigated. Results: A total of 54 eyes of 54 patients who underwent PK (32 eyes/32 patients) and DSAEK (22 eyes/22 patients) were evaluated, and suspected immune cells were observed in all patients. In the PK and DSAEK groups, the number of patients in the presumed immune cell grades 1, 2, 3, and 4 were 19, 10, 2, and 1 and 10, 8, 2, and 2, respectively ( P = 0.663). No statistically significant association was found between the immune cell grades and the clinical parameters. Conclusions: Immune cells were observed on the corneal endothelial grafts in all 54 patients who underwent PK or DSAEK. Although the number of immune cells varied between patients and showed no correlation with clinical parameters, it would be beneficial to conduct a future prospective study to analyze the effect of immune cells on postoperative corneal endothelial cell loss. Abstract : Supplemental Digital Content is Available in the Text.